2021
DOI: 10.1002/celc.202100250
|View full text |Cite
|
Sign up to set email alerts
|

Selective Enhancement of Electrochemical Signal Based on the Size of Alcohols Using Nanoporous Platinum

Abstract: Nanoporous electrodes are representative electrode materials for diverse applications, such as energy conversion devices and sensors. Recently, selectivity based on the size of ions arising from nanoporous structures has been applied to capacitive deionization, electrochemical supercapacitors, and conductometry. Herein, we explored the selectivity based on the size of the redox molecules on the electrochemical reaction at the nanoporous Pt electrode with extremely small (1-2 nm) and uniform pores by linear swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Prior to use, the solution was purged with high-purity nitrogen gas for approximately 5 min, and a nitrogen environment was maintained throughout the experiments. For cyclic voltammetry, as the scan rate increases, the reaction efficiency of the reactants within the nanoporous electrode decreases, so a relatively slow scan rate of 10 mV s –1 was used . For electrochemical impedance spectroscopy (EIS) experiments, a Reference 600+ system equipped with EIS300 electrochemical impedance spectroscopy software (Gamry Instruments) was utilized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to use, the solution was purged with high-purity nitrogen gas for approximately 5 min, and a nitrogen environment was maintained throughout the experiments. For cyclic voltammetry, as the scan rate increases, the reaction efficiency of the reactants within the nanoporous electrode decreases, so a relatively slow scan rate of 10 mV s –1 was used . For electrochemical impedance spectroscopy (EIS) experiments, a Reference 600+ system equipped with EIS300 electrochemical impedance spectroscopy software (Gamry Instruments) was utilized.…”
Section: Methodsmentioning
confidence: 99%
“…Advances in the fabrication of nanoporous electrodes with uniform pore structures have led to the application of nanoporous electrodes in electrochemical reactions, such as catalysis and sensors. Research on novel electrochemical phenomena induced by the structure of nanoporous electrodes has been actively conducted in recent years. Nanoporous materials are also attracting attention as a way to easily impart selectivity to electrodes, and selectivity studies utilizing the nanoconfined structure of nanoporous electrodes have been mainly characterized by the reaction rate, size, and charge of the reactants. In other words, the slower the reaction rate, the smaller the size of the reactant species, and the deeper the reactant species that can enter the nanopore, the more selectively the electrochemical signal can be amplified. In addition, a study has been reported on imparting selectivity by introducing reactants with opposite charges to the electrodes into the nanopores by using the electric double-layer overlapping phenomenon in the nanopore electrodes. , …”
Section: Introductionmentioning
confidence: 99%
“…Next, solid-state RE was fabricated on the nanoporous Pt via electropolymerization of poly-1,3-phenylenediamine (poly-m-PD). The nanoporous Pt film with uniform pores of 1-2 nm named L 2 -ePt was fabricated by electrochemically plating Pt in a reverse micelle solution formed by using a surfactant as a template reported in our previous papers [18][19][20][21][22][23]36]. Chloroplatinic acid hexahydrate (5 wt%), Triton X-100 (50 wt%), and 0.3 M sodium chloride (45 wt%) were mixed and heated at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The exchange current of a nanoporous electrode is much higher than that of the flat electrode with apparently the same area because the nanoporous electrode drastically enlarges the interfacial area between the electrode surface and the sample solution. Previously, we have demonstrated the utility of nanoporous Pt in various applications such as electrocatalysis, electroanalysis, and neural probes [18–23]. The large surface area of nanoporous Pt leads to a very low polarizability in the electrochemical reactions according to the following equation (1) [24]: PtOnormalx+2δH++2δe-PtOx-δ+δH2O $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm PtO}{_{{\rm x}}}+2{\rm \delta} {\rm H}{^{+}}+2{\rm \delta} {\rm e}{^{- }}{\stackrel{ {\rightarrow} } { {\leftarrow} } } {\rm PtO}{_{{\rm x}\hbox{-}{\rm \delta} }}+{\rm \delta} {\rm H}{_{2}}{\rm O}\hfill\cr}}$ …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation